Wedding planner application using augmented reality - Leong, Jia Xuan (2021)
This project is intended to develop a wedding planner application with integrated Augmented Reality (AR) technology. The main purpose of developing this mobile app called “WedDream” is to realise people’s dream wedding by providing them with a number of functional features. Before defining the project scope and requirements, several applications like The Big Day, LadyMarry and MyWed that available in the market are selected to be studied. This action contributes into the inspiration and motivation of WedDream app. In order to improve the performance of existing wedding planner applications, this project has merged the basic planning features and AR venue design function into a single application. The fundamental modules implemented is including the checklist, budget, guest list and countdown features. To develop an interactive and practical application, Agile Software Development approach is adopted due to its effectiveness in coping with the frequent changing demands. In this project, Android Studio is chosen to build the framework of mobile app and other functional modules by using Java language. Nevertheless, the AR venue design module is being developed with Unity game engine along with AR Foundation framework and ARCore Extensions package which supports the AR functionality. In addition, the core language for implementing AR technology is C# programming language. As a result, this project is believed to assist users in planning their big day and design a fantasy wedding venue according to their desired style.